READER RESPONSE AND AI-BASED LITERARY LEARNING: A PSYCHOLOGICAL-EXISTENTIAL CASE STUDY IN MODERN INDONESIAN LITERATURE - Saraswati, Ekarini (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This essay introduces a novel pedagogical approach for instructing modern Indonesian literature through the integration of Reader Response Theory and artificial intelligence. This analysis emphasizes psychological and existential problems in Armijn Pane’s Belenggu, Y.B. Mangunwijaya’s Burung-Burung Manyar, and Laksmi Pamuntjak’s Amba, while prioritizing students’ individual interpretations. AI instruments—sentiment analysis, reflective chatbots, and prompt generators—facilitate profound, adaptive contemplation. The study used a descriptive qualitative approach that integrates a literature review and organized classroom observation, revealing that AI-assisted reader response enhances engagement in emotive, cognitive, and creative domains. An examination of five pivotal passages from each work reveals that students more easily relate the characters’ conflicts with identity, history, love, and freedom to their personal experiences, fostering empathy and self-awareness. AI facilitates immediate feedback and customized pathways tailored to individual learner profiles. This approach expands literary pedagogy and cultivates readers’ awareness of their role within texts and the world, providing a reflective and adaptable model appropriate for twenty-first-century education and classrooms.